Issues Of Legal Identification Of The Status Of The Human Genome - Yernar Shalkharov, Azhar Nartay,; Galymzhan Ernazarov, Kairat Bitemirov, Manshuk Imanbekova, (Opción, 2019)
This article aims to identify the legal status of the human genome as a whole, classify areas of interaction, and differentiate variables of law and ethics via techniques related to an interdisciplinary approach that involve regression, inverse correlation. As a result, a smaller percentage of 18.6% of respondents suggested that human genetic material can be considered as an object of commercial turnover in the modern market space. In conclusion, one can indicate a certain kind of changes in the field of development of legislation regarding genetic engineering associated with the fields of transplantology, oncology, embryology and other similar sciences.